Report of a Case of Peripheral Giant Cell Granuloma in Anterior Maxillary Region - P Moeiny; S Shabani; M Vatankhah; A bakhshi; M Zameni (Islamic Azad University, 2019)
Background: Gingival overgrowth is a common clinical finding that most often represents reactive hyperplasia as a result of inflammatory gingival disease related to dental plaque. Irritation fibroma (IF), pyogenic granuloma (PG), peripheral ossifying fibroma (POF), and peripheral giant cell granuloma (PGCG) are non-neoplastic enlargements of the gingiva that are categorized as reactive hyperplastic lesions. Most of these lesions have a similar clinical appearance, i.e., a sessile or pedunculated nodule at the interdental papilla; the color varies from pale pink to red. All reactive gingival lesions show some variations in terms of gender, type, location, duration, and histologic features. Case Presentation: Here, we present a case of PGCG in a 10-year-old male with its clinical presentations as well as radiological and histological features along with the management procedure. Conclusion: Choice of treatment for our case was surgical excision, fluoride therapy, and oral hygiene maintenance. The patient remained tumor-free for 18 months and is still on regular follow-up.